2015
DOI: 10.1038/hr.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness and elastic properties of aortas in normotensive children of hypertensive parents

Abstract: A significant correlation between hypertension history and high blood pressure has been observed with regard to age, race and gender. Investigating carotid intima-media thickness and aortic stiffness prior to the development of hypertension in children of hypertensive parents enabled us to evaluate these patients for subclinical atherosclerosis. We compared carotid intima-media thickness, aortic strain, distensibility, stiffness indices and elastic modulus in 67 normotensive children whose parents had a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In that study, when the children were divided into age groups, systolic blood pressure after 15 years of age was reported to be higher in the study group compared to the control group. 31 A few studies in the literature have demonstrated that children of hypertensive parents have increased blood pressure and arterial stiffness compared to children of normotensive parents, which is more pronounced in the adolescent period. 2,15,[26][27] In this study, pulse wave velocity was higher in normotensive children of hypertensive parents compared to the control group in all age groups, whereas in the post-puberty period (15-18 years), systolic blood pressure, mean arterial pressure, pulse pressure, and central systolic blood pressure, as well as pulse wave velocity, was significantly higher in the study group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, when the children were divided into age groups, systolic blood pressure after 15 years of age was reported to be higher in the study group compared to the control group. 31 A few studies in the literature have demonstrated that children of hypertensive parents have increased blood pressure and arterial stiffness compared to children of normotensive parents, which is more pronounced in the adolescent period. 2,15,[26][27] In this study, pulse wave velocity was higher in normotensive children of hypertensive parents compared to the control group in all age groups, whereas in the post-puberty period (15-18 years), systolic blood pressure, mean arterial pressure, pulse pressure, and central systolic blood pressure, as well as pulse wave velocity, was significantly higher in the study group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported blood pressure was similar in the 18–22-year-old children of hypertensive and normotensive parents but aortic stiffness parameters were higher in the former group [ 29 ]. In our previous study we found that an increase in the carotid intima-media thickness in children of hypertensive parents may indicate subclinical atherosclerosis [ 30 ]. Children of hypertensive parents may first experience hormonal and biochemical changes, followed by the development of damage to the endothelial and vascular structures and subsequent cardiac compensation, with hypertension only appearing at latter stages.…”
Section: Discussionmentioning
confidence: 99%